Pemanfaatan Whatsapp sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Fisika - Somantri, Sandi (UPEJ Unnes Physics Education Journal, 2019)
This research aims to improve student learning outcomes by utilizing WhatsApp. This research uses Classroom Action Research (CAR) with teachers as researchers and educators in the class. The study was implemented in class X TBSM 4 Tasikmalaya Vocational High School in the first semester of the 2018/2019 academic year which is a non-main place where researchers teach with subjects 30 students. This research lasts for three cycles with one cycle studying different one basic competency. Each cycle consists of the following steps: (1) Planning, (2) acting, (3) observing, (4) reflecting. The learning process uses a variety of learning models including discovery learning, problem based learning, and project based learning. Each learning model uses various methods including demonstrations, talking, discussions, and question and answer. Data obtained from the results of documentation, observation, questionnaires, and written tests. Assessment is done in two ways, directly in class and outside the classroom through the WhatsApp application. The results of research indicate that there is an increase in learning outcomes in each cycle. Learning outcomes of students in the third cycle reached above the minimum completeness criteria so it can be concluded that the WhatsApp application can be used to improve student learning outcomes in class X TBSM 4 of Tasikmalaya in the first semester of the 2018/2019 academic year.